2022
DOI: 10.3390/pharmaceutics15010059
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors for Glioblastoma Multiforme: Challenges and Opportunities for Drug Delivery

Abstract: Glioblastoma multiforme (GBM) is an aggressive brain tumor with high mortality rates. Due to its invasiveness, heterogeneity, and incomplete resection, the treatment is very challenging. Targeted therapies such as tyrosine kinase inhibitors (TKIs) have great potential for GBM treatment, however, their efficacy is primarily limited by poor brain distribution due to the presence of the blood–brain barrier (BBB). This review focuses on the potential of TKIs in GBM therapy and provides an insight into the reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 165 publications
1
19
0
1
Order By: Relevance
“…Even though good tolerability was reported, therapy with Gefitinib failed for most participants in the first 8-week evaluation of a phase II clinical trial for recurrent GBM [ 152 ]. Previous benefits shown in preclinical studies were also not confirmed in clinical trials with Erlotinib, as monotherapy or in combination [ 38 , 146 ].…”
Section: New Therapies For the Treatment Of Gbmmentioning
confidence: 93%
See 4 more Smart Citations
“…Even though good tolerability was reported, therapy with Gefitinib failed for most participants in the first 8-week evaluation of a phase II clinical trial for recurrent GBM [ 152 ]. Previous benefits shown in preclinical studies were also not confirmed in clinical trials with Erlotinib, as monotherapy or in combination [ 38 , 146 ].…”
Section: New Therapies For the Treatment Of Gbmmentioning
confidence: 93%
“…Tyrosine kinase (TK) proteins are a large, multigene family of proteins, whose function is related to the regulation of cell-to-cell signaling. They can be found in cell membranes or in the cytoplasm and are classified as TK receptors or non-receptors, respectively [ 146 ]. TK proteins play important roles in diseases such as cancer and diabetes, mostly due to their function as regulators of cellular processes and homeostasis [ 146 , 147 ].…”
Section: New Therapies For the Treatment Of Gbmmentioning
confidence: 99%
See 3 more Smart Citations